Accessing contested landscapes: a political ecology of tree planting in the Lake District - Wallerand Bazin (Mondes du Tourisme)
This article analyses the socio-political implications of the Lake District’s ‘landscape transition’ amidst an acceleration of tree planting efforts within the National Park. Cradle to English Romanticism and flagship destination for national and international tourism, the Lake District’s UNESCO World Heritage cultural landscape is the site of ongoing negotiations between tourist, environmental and agropastoral actors over what counts as ‘natural’ and ‘cultural’. At the crossroads between political ecology and cultural geography, this article analyses how tree planting reconfigures the ‘original’ landscape attracting 18 million tourists a year and unsettles public access to reforested uplands. In doing so, it sheds light on the socio-cultural obstacles that touristic landscapes must face when implementing ecological landscape transitions.